2003
DOI: 10.1002/jso.10287
|View full text |Cite
|
Sign up to set email alerts
|

A new proliferation marker, minichromosome maintenance protein 2, is associated with tumor aggressiveness in esophageal squamous cell carcinoma

Abstract: MCM2 may be a more reliable and useful marker than Ki-67 in assessing the growth of normal and tumor cells and in evaluating tumor aggressiveness and prognostic value in patients with esophageal SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
46
0
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 24 publications
7
46
0
8
Order By: Relevance
“…Expression of MCM proteins detected by immunohistochemistry predicts survival in patients with breast cancer [27], brain tumours [28,29], non-small cell lung cancer [30,31], prostate cancer [32], bladder [33], oesophageal [34], renal cell [35], and oral squamous cell carcinoma [36]. Consistent with these findings, MCM genes have also been found to be up-regulated at the mRNA level in a range of malignancies by expression microarray analysis.…”
Section: Proteins As Diagnostic Prognostic and Predictive Tumoumentioning
confidence: 62%
“…Expression of MCM proteins detected by immunohistochemistry predicts survival in patients with breast cancer [27], brain tumours [28,29], non-small cell lung cancer [30,31], prostate cancer [32], bladder [33], oesophageal [34], renal cell [35], and oral squamous cell carcinoma [36]. Consistent with these findings, MCM genes have also been found to be up-regulated at the mRNA level in a range of malignancies by expression microarray analysis.…”
Section: Proteins As Diagnostic Prognostic and Predictive Tumoumentioning
confidence: 62%
“…To date, most studies have focused on MCM2 expression alone. A high level of MCM2 proteins was linked to advanced stages of breast cancer, non-small-cell lung carcinoma, esophageal squamous cell carcinoma, colorectal cancer, gliomas and urothelial carcinoma (Ramnath et al, 2001;Wharton et al, 2001;Rodins et al, 2002;Gonzalez et al, 2003;Kato et al, 2003;Korkolopoulou et al, 2005;Scott et al, 2005;Hanna-Morris et al, 2009). The aberrant expression of MCM2 was also correlated with poor prognosis in patients (Meng et al, 2001;Ramnath et al, 2001;Wharton et al, 2001;Rodins et al, 2002;Korkolopoulou et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies and expression microarray analyses have independently identified MCM proteins as powerful indicators of worse clinical outcome in various tumour types (Meng et al, 2001;Ramnath et al, 2001;Wharton et al, 2001;Hunt et al, 2002;Rodins et al, 2002;van 't Veer et al, 2002;Gonzalez et al, 2003;Kato et al, 2003;Kodani et al, 2003;Kruger et al, 2003;Rosenwald et al, 2003;Sotiriou et al, 2003;Hashimoto et al, 2004;Neben et al, 2004;Yu et al, 2004a;Korkolopoulou et al, 2005;Shetty et al, 2005). The MCM genes have also appeared as part of 'poor' prognostic signatures in breast cancer (van 't Veer et al, 2002;Sotiriou et al, 2003;Yu et al, 2004a), mantle cell lymphoma (Rosenwald et al, 2003) and medulloblastoma (Neben et al, 2004), whereas in cervical cancer, MCM protein expression appears promising as a predictor of response to radiation therapy (Mukherjee et al, 2001).…”
Section: Discussionmentioning
confidence: 99%